2021
DOI: 10.1111/jonm.13388
|View full text |Cite
|
Sign up to set email alerts
|

Workplace bullying and different levels of post‐traumatic stress symptoms of nurses: A quantile regression approach for effective coping strategies

Abstract: Aim This study aimed to investigate effects of workplace bullying on different post‐traumatic stress symptoms and coping among hospital nurses. Background Workplace bullying is a traumatic event that negatively affects the quality of patient care and nurses’ mental health. Method This cross‐sectional, correlational study used an online survey among hospital nurses. Ordinary least square and quantile regression analyses were conducted using Stata version 16. Results The study included 233 registered nurses from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 28 publications
5
20
0
Order By: Relevance
“…As suggested by Lucena et al [ 38 ], in the health care sector, workers in environment characterized by WPB are willing to accept the problem and suggest that victims ignore the problem (downplaying and denying the misconduct) or make a positive break (e.g., behaving differently in the workplace). These findings were confirmed by Wunnenberg [ 35 ] and Hong et al [ 39 ]. In the study conducted by Wunnenberg [ 36 ], the results showed that nurses in a WPB context use a variety of coping strategies, including trying to solve the problem, seeking social support (e.g.…”
Section: Background - Wpb In Health Care Facilitiessupporting
confidence: 74%
“…As suggested by Lucena et al [ 38 ], in the health care sector, workers in environment characterized by WPB are willing to accept the problem and suggest that victims ignore the problem (downplaying and denying the misconduct) or make a positive break (e.g., behaving differently in the workplace). These findings were confirmed by Wunnenberg [ 35 ] and Hong et al [ 39 ]. In the study conducted by Wunnenberg [ 36 ], the results showed that nurses in a WPB context use a variety of coping strategies, including trying to solve the problem, seeking social support (e.g.…”
Section: Background - Wpb In Health Care Facilitiessupporting
confidence: 74%
“…For hospital nurses, the aspects of the work environment that contribute to workplace violence include shift‐based work, demanding workloads, inadequate organisational support, a hierarchical structure, and frequent emergency situations (Al‐Maskari et al, 2020; International Council of Nurses, 2017; Ministry of Health and Welfare of South Korea, 2018). Although previous studies have examined the occurrences of workplace violence, violence‐related factors such as job outcomes, and health effects of nursing occupation, few studies have compared occupational contexts of violence (Al‐Maskari et al, 2020; Chang & Cho, 2016; Ebrahimi et al, 2017; Hong, Kim, Choi, & Park, 2021; Hong, Kim, Nam, et al, 2021). Comparing workplace violence in other occupations to workplace violence in the nursing profession can help identify the characteristics unique to workplace violence among nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Ten studies did not specify the perpetrator but reported the highest level of anxiety (Duru et al, 2018; Shi et al, 2018), emotional exhaustion (Sui et al, 2019; Tong et al, 2019), burnout, depression (X. Li & Wu, 2021; Sui et al, 2019) and stress (Chan et al, 2008; Hong et al, 2021; Pien et al, 2015; Shaffer et al, 2000). Mistreatment triggered higher levels of negative affect ( r = .29, p < .001) and anger r . = 0.15) compared to negative mood ( r = .10, p < .05).…”
Section: Resultsmentioning
confidence: 99%